Intrapreneurial spaces to entrepreneurial cities: Making sense of play and playfulness. (May 2018) - Dobson, Stephen; McKendrick, John
By drawing upon a diverse range of literature, this article aims to set out play and playfulness as an under-researched area in entrepreneurship. The conceptual lens applied is that of space and the city, from playfulness as a means to support intrapreneurial activity in the organization through to play and playfulness in the urban environment. This position paper aims to emphasize potential areas for research as pertinent to the special issue and, along with the collection of papers present here, aims to highlight news avenues for research into the space for creativity and entrepreneurial activity conceptualized as an extension of play.